DROP SIZE AND DISPERSED PHASE HOLDUP IN A SPRAY COLUMN - SAEED, MUHAMMAD TARIQ; JAMIL, MUHAMMAD (Biological Sciences - PJSIR, 2022)
Drop size and dispersed phase holdup in a spray column for a reactive extraction system (zinc/di (2-ethylhexyl) phosphoric acid) has been obtained under solute transfer from continuous to dispersed and dispersed to continuous phase. A photographic method is used for the estimation of drop size and dispersed phase holdup. The experiments are carried out in a glass spray column operated under semi-batch mode, i.e. the continuous aqueous phase is kept stagnant and the dispersed phase is not recirculated. Dispersed phase velocity through the nozzles is varied from 3.4 x 10-2 to 24.5xlO-2 m/s. Nozzle diameter ranges from 0.8 x 10-3 to 3 x la-3m.